Are Vancomycin Trough Concentrations of 15 to 20 mg/L Associated With Increased Attainment of an AUC/MIC ≥ 400 in Patients With Presumed MRSA Infection?. (June 2017) - Hale, Cory M.; Seabury, Robert W.; Steele, Jeffrey M.; Darko, William; Miller, Christopher D.
Purpose: To determine whether there is an association between higher vancomycin trough concentrations and attainment of a calculated area under the concentration–time curve (AUC)/minimum inhibitory concentration (MIC) ≥400. Methods: A retrospective analysis was conducted among vancomycin-treated adult patients with a positive methicillin-resistant Staphylococcus aureus (MRSA) culture. Attainment of a calculated AUC/MIC ≥400 was compared between patients with troughs in the reference range of 15 to 20 mg/L and those with troughs in the following ranges: <10, 10 to 14.9, and >20 mg/L. Nephrotoxicity was assessed as a secondary outcome based on corrected average vancomycin troughs over 10 days of treatment. Results: Overall, 226 patients were reviewed and 100 included. Relative to troughs ≥10, patients with vancomycin troughs <10 mg/L were 73% less likely to attain an AUC/MIC ≥400 (odds ratio [OR] 0.27, 95% confidence interval [CI]: 0.01-0.75). No difference was found in the attainment of an AUC/MIC ≥400 in patients with troughs of 10 to 14.9 mg/L and >20 mg/L when compared to patients with troughs of 15 to 20 mg/L. The mean corrected average vancomycin trough was higher in patients developing nephrotoxicity compared to those who did not (19.5 vs 14.5 mg/L, P < .001). Conclusion: Achieving vancomycin serum trough concentrations of 15 to 20 mg/L did not result in an increased attainment of the AUC/MIC target relative to troughs of 10 to 14.9 mg/L but may increase nephrotoxicity risk.